Photocatalytic degradation of water pollutants using II-VI semiconducting catalysts: A comprehensive review. Issue 6 (December 2021) - Gupta, Tripti; Chauhan, R.P.
Abstract: II-VI semiconductors have forged expeditious improvement in numerous applications such as catalysis, gas sensors, degradation of dyes, drug delivery, and so on. Currently, most of the researchers are engrossed in II-VI compounds for their photocatalytic activity, since the utilization of proficient and economical nano-adsorbent for the exclusion of contaminants from wastewater has become the imperative topic of research, as far as the environment is concerned. This review succinctly outlines an in-depth appraisal of extensive variety of II-VI adsorbents reported in the literature for water purification along with endorsing the mechanism involved. A holistic approach of comparison of degradation efficiencies under different operating conditions is undertaken to quest for suitable adsorbents. Furthermore, doped II-VI compounds and advanced heterostructures designed to date to achieve sky-scrapping efficiencies are furnished. The critical evaluation of next-generation photocatalysts would apparently be nurtured for the clean and thrifty water purification process in the near future. Graphical Abstract: ga1 Highlights: II-VI nanostructures are reviewed for the sustainable mitigation of effluents from water sources. The trends in the publication of popular II-VI semiconductors from the past decade are scrutinized. Modification strategies are elucidated which can be considered in the future to enhance the degradation efficiency of photocatalysts.